Breast implant-associated anaplastic large-cell lymphoma: a systematic literature review - Daniel Sundfeld Spiga Real; Beatriz Sant'ana Resendes (Revista Brasileira de Cirurgia Plástica, 2019)
Breast implant-associated anaplastic large-cell lymphoma (BIA-ALCL) is a newly discovered and rare cancer possibly associated with textured breast implants. This literature review investigates its epidemiology, pathophysiology, and risk factors. PubMed, LILACS, and SciELO databases were searched from December 2018 to February 2019, and 10 articles published between 2016 and 2018 were selected. The incidence of BIA-ALCL ranged from 2.8:100,000 to 1:3 million breast implants. The obtained data corroborate the hypothesis that there is no direct cause and effect relationship between breast implants, especially textured implants, and BIA-ALCL, and these implants can be considered risk factors but not causative factors. The most accepted hypothesis on disease pathophysiology is that breast implants with larger surface areas may promote bacterial adhesion and biofilm formation, leading to severe chronic inflammation, triggering the malignant transformation of T cells. This review provides knowledge on BIA-ALCL and helps develop and implement public policies for disease prevention and timely diagnosis. The data highlight that long-term follow up is necessary and that surgeons should advise patients of the potential risk of developing BIA-ALCL before performing the implant surgery.